All-cause mortality and location of death in patients with established cardiovascular disease before, during, and after the COVID-19 lockdown: a Danish Nationwide Cohort Study - Butt, Jawad H; Fosbøl, Emil L; Gerds, Thomas A; Andersson, Charlotte; Kragholm, Kristian; Biering-Sørensen, Tor; Andersen, Julie; Phelps, Mathew; Andersen, Mikkel Porsborg; Gislason, Gunnar; Torp-Pedersen, Christian; Køber, Lars; et al. (European heart journal, 2021)
On 13 March 2020, the Danish authorities imposed extensive nationwide lockdown measures to prevent the spread of the coronavirus disease 2019 (COVID-19) and reallocated limited healthcare resources. We investigated mortality rates, overall and according to location, in patients with established cardiovascular disease before, during, and after these lockdown measures. Using Danish nationwide registries, we identified a dynamic cohort comprising all Danish citizens with cardiovascular disease (i.e. a history of ischaemic heart disease, ischaemic stroke, heart failure, atrial fibrillation, or peripheral artery disease) alive on 2 January 2019 and 2020. The cohort was followed from 2 January 2019/2020 until death or 16/15 October 2019/2020. The cohort comprised 340 392 and 347 136 patients with cardiovascular disease in 2019 and 2020, respectively. The overall, in-hospital, and out-of-hospital mortality rate in 2020 before lockdown was significantly lower compared with the same period in 2019 [adjusted incidence rate ratio (IRR) 0.91, 95% confidence interval (CI) CI 0.87-0.95; IRR 0.95, 95% CI 0.89-1.02; and IRR 0.87, 95% CI 0.83-0.93, respectively]. The overall mortality rate during and after lockdown was not significantly different compared with the same period in 2019 (IRR 0.99, 95% CI 0.97-1.02). However, the in-hospital mortality rate was lower and out-of-hospital mortality rate higher during and after lockdown compared with the same period in 2019 (in-hospital, IRR 0.92, 95% CI 0.88-0.96; out-of-hospital, IRR 1.04, 95% CI1.01-1.08). These trends were consistent irrespective of sex and age. Among patients with established cardiovascular disease, the in-hospital mortality rate was lower and out-of-hospital mortality rate higher during lockdown compared with the same period in the preceding year, irrespective of age and sex.